CO2 emission abatement cost and its decomposition: A directional distance function approach. (1st January 2018) - Wang, Yizhong; Wang, Qunwei; Hang, Ye; Zhao, Zengyao; Ge, Shilong
Abstract: Accurately estimating carbon dioxide (CO2 ) abatement costs, and effectively identifying the factors impacting those costs, can improve the applicability and effectiveness of policy implementation. This paper proposes a new method to estimate CO2 abatement costs (CAC) based on the directional distance function. The method theoretically decomposes CAC into carbon productivity and output elasticity of substitutions; this decomposition can identify the types of CAC. The method also investigates the effects of development mode selection on CAC, by selecting different directional vectors. Following the theoretical discussion, an empirical study is presented, focusing on high energy-consumption firms in the United States (U.S). The results were as follows. (1) In sustainable development mode, changes in the average CAC of all firms were caused both by carbon productivity and output elasticity of substitution. Carbon productivity dominated CAC differences among different firm types. (2) In general, the amelioration potential of firm technology and environmental management was gradually explored by firms during sample period; corresponding environmental regulatory strategies are needed for firms with different CAC characteristics. (3) Firms selecting different development modes will realize significant differences in CAC. Firms in the sustainable development mode had the highest CAC levels; however, this mode was best for achieving a win-win between economic benefits and environmental protection. Highlights: A new approach to estimate CO2 emission abatement costs (CAC) is proposed. CAC can be decomposed into carbon productivity and elasticity of output substitutions. Carbon productivity dominates the difference of CAC among firms in U.S. Development mode has significant influence on CAC of firms in U.S.